Sero-prevalence of Herpes Simplex Type 2 Virus (HSV-2) and HIV Infection in Kampala, Uganda - Nakku-Joloba, Edith; Kambugu, Fred; Wasubire, Julius; Kimeze, Joshua; Salata, Robert; Albert, Jeffrey M.; Rimm, Alfred; Whalen, Christopher (African health sciences, 2014)
Prevalence of herpes simplex type 2 virus (HSV-2) is high worldwide. Previous studies in Uganda were rural or in women. We estimated age and sex-specific sero- prevalence of HSV-2 in Kampala, Uganda.Using two-stage random sampling stratified on population density, a survey of persons 15-65 years was conducted. Type-specific serological tests for HSV-2, HSV-1(HerpeSelect2 and 1 ELISA), HIV (Rapid tests and ELISA), syphilis (RPR and TPHA) were done. Additional prevalence analysis included post-stratification weighting on the Uganda 2002 Census gender distribution.Among 1124 persons, HSV-2 prevalence was 58% (95% CI: 55, 60), HSV-1; 98% (95% CI: 97.6, 99.1), HIV; 17.7% (95% CI: 14.8, 19.2) and syphilis; 1.7% (95% CI: 1.4, 1.9). Weighted HSV-2 prevalence was 53.8% (Women; 63.8%, men; 43.2%), similar to unweighted data. Weighted HIV prevalence was 20.7% in women, 8.6% in men. Of 165 HIV infected persons, 85.4% had HSV-2. Risk factors for HSV-2 were being a woman (OR 2.0; 95% CI: 1.42, 2.78), age (OR 3.3; 95% CI: 2.43, 4.53), education (OR 1.70; 95% CI: 1.34, 2.34) and HIV (OR 4.5; 95% CI: 2.70, 7.50).Prevalence of HSV-2 and HIV was high especially in women. Syphilis was rare. Awareness of herpes was low. Interventions in young people are needed.
Keywords: HSV-2, HIV, Kampala Uganda